Pet sematary (1989) [videorecording (DVD)] - Lambert, Mary (Mary M.); Gwynne, Fred; Midkiff, Dale, 1959-; Crosby, Denise; King, Stephen, 1947- (Paramount, 2017)
The Creeds move next door to a pet cemetery, which is built over old Native American burial grounds with the power of resurrection.